The pharmacokinetics of vancomycin during the initial loading dose in patients with septic shock - Katip W. (2017)
© 2016 Katip et al. Objective: To characterize the pharmacokinetics (PK) of vancomycin in patients in the initial phase of septic shock. Methods: Twelve patients with septic shock received an intravenous infusion of vancomycin 30 mg/kg over 2 h. The vancomycin PK study was conducted during the first 12 h of the regimen. Serum vancomycin concentration-time data were analyzed using the standard model-independent analysis and the compartment model. Results: For the noncompartment analysis the mean values ± standard deviation (SD) of the estimated clearance and volume of distribution of vancomycin at steady state were 6.05±1.06 L/h and 78.73±21.78 L, respectively. For the compartmental analysis, the majority of vancomycin concentration-time profiles were best described by a two-compartment PK model. Thus, the two-compartmental first-order elimination model was used for the analysis. The mean ± SD of the total clearance (3.70±1.25 L/h) of vancomycin was higher than that obtained from patients without septic shock. In contrast, the volume of the central compartment (8.34±4.36 L) and volume of peripheral compartment (30.99±7.84 L) did not increase when compared with patients without septic shock. Conclusion: The total clearance of vancomycin was increased in septic shock patients. However, the volume of the central compartment and peripheral compartment did not increase. Consequently, a loading dose of vancomycin should be considered in all patients with septic shock.